A New Perspective on Relativity Theory (Global Journal of Science Frontier Research, 2024)
The particular theory of relativity was created by Albert Einstein in 1905. As the starting point for this theory, he adopted two principles from the beginning: the "principle of relativity" and the "principle of the constancy of the velocity of light." Later, when it was pointed out that the velocity of light changes within the solar system (in a gravitational field), he argued that the velocity of light does not appear to be constant due to the "spatial distortion." He then constructed the general theory of relativity that took into account the "spatial distortion."
Keywords: particular relativity theory; general relativity theory